Khalifa Abdul Hakim on the Doctrine of Free Will and Predestination, Good and Evil in Islam - Hafiz Muhammad Saleem; Khurshidul Hasan Rizvi (بازیافت, 2019)
Dr. Khalīfah Abdul Hakim, (1896- 1959) has done his utmost effort to present the values of Islam and its various doctrines in the garb of Philosophy. This article is a comprehensive enunciation of Dr. Khalīfah Abdul Hakim’s approach to the Doctrine of Free will and Predestination, Good and Evil in Islam. Khalīfah says that man is endowed with free will. If he were merely a part of nature which is  determined by fixed laws, he would not be different from matter and plants. Furthermore, God is free and when he made him in His own image and breathed His own spirit into him, as the Qur’an teaches, He made him also free. But, freedom is a double- edged weapon. If the granting of free will to man is an act of a loving fosterer, then any evil that may result from it cannot be attributed to lack of goodness in the Creator. Man can revolt even against his Creator. He is not created with perverted instincts. The theory of original sin is absolutely incompatible with the teachings of Islam. So far as the theory of existence of evil in nature is concerned, Khalīfah has categorically repudiated it as there is no flaw in nature. It is only our desires that attributed good or evil to the happenings of nature. There is no natural evil but there certainly exists moral evil as a result of the gift of free will to man. However, there are two kinds of moral evil. First, the evil caused by man’s own acts. Second, the evil caused by the acts of others. The sufferings caused by man’s own acts are actually the result of his endowed free will. The sufferings caused by the acts of others are the source of man’s purification.